Radiation-Associated Toxicities in Obese Women with Endometrial Cancer: More Than Just BMI? - Savita V. Dandapani; Ying Zhang; Richard Jennelle; Yvonne G. Lin (The Scientific World Journal)
Purpose. The study characterizes the impact of obesity on postoperative radiation-associated toxicities in women with endometrial cancer (EC). Material and Methods. A retrospective study identified 96 women with EC referred to a large urban institution’s radiation oncology practice for postoperative whole pelvic radiotherapy (WPRT) and/or intracavitary vaginal brachytherapy (ICBT). Demographic and clinicopathologic data were obtained. Toxicities were graded according to RTOG Acute Radiation Morbidity Scoring Criteria. Follow-up period ranged from 1 month to 11 years (median 2 years). Data were analyzed by χ2, logistic regression, and recursive partitioning analyses. Results. 68 EC patients who received WPRT and/or ICBT were analyzed. Median age was 52 years (29–73). The majority were Hispanic (71%). Median BMI at diagnosis was 34.5 kg/m2 (20.5–56.6 kg/m2). BMI was independently associated with radiation-related cutaneous (p=0.022) and gynecologic-related (p=0.027) toxicities. Younger women also reported more gynecologic-related toxicities (p=0.039). Adjuvant radiation technique was associated with increased gastrointestinal- and genitourinary-related toxicities but not gynecologic-related toxicity. Conclusions. Increasing BMI was associated with increased frequency of gynecologic and cutaneous radiation-associated toxicities. Additional studies to critically evaluate the radiation treatment dosing and treatment fields in obese EC patients are warranted to identify strategies to mitigate the radiation-associated toxicities in these women.